2008
DOI: 10.1111/j.1742-1241.2008.01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin detemir improves glycaemic control without weight gain in insulin-naïve patients with type 2 diabetes: subgroup analysis from the PREDICTIVETM study

Abstract: Patients with type 2 diabetes naïve to insulin can be effectively treated with once-daily insulin detemir (+/- OADs) to achieve improved glycaemic control with no adverse effect on weight and a low risk of hypoglycaemia. These short-term results are consistent with the findings of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 20 publications
9
58
2
3
Order By: Relevance
“…25,32,33 They are also consistent with clinical trial data of insulin detemir in comparison to other insulin types and can be relevant to routine clinical practice. 5,16,22 Consequently, insulin therapies like insulin detemir, which are better able to mimic the body's physiological responses, provide some scope for achieving an improved balance between glycemic control and treatment tolerability.…”
Section: Insulin Detemir In T2dm -Echtay Et Alsupporting
confidence: 63%
See 1 more Smart Citation
“…25,32,33 They are also consistent with clinical trial data of insulin detemir in comparison to other insulin types and can be relevant to routine clinical practice. 5,16,22 Consequently, insulin therapies like insulin detemir, which are better able to mimic the body's physiological responses, provide some scope for achieving an improved balance between glycemic control and treatment tolerability.…”
Section: Insulin Detemir In T2dm -Echtay Et Alsupporting
confidence: 63%
“…12 Although clinical trials support flexibility in injection frequency (once or twice daily), the pharmacodynamics profile of insulin detemir is best suited to once-daily use in persons with T2DM. 32 While data on frequency of injections was not collected in this study, similar studies with insulin detemir ± OADs showed that a once-daily injection was adequate for good glycemic control in the majority of persons (77% to 82%) with <25% persons requiring twice daily injections after 14 weeks of insulin detemir ± OADs. 25,31 Accordingly, an increase in the mean daily dose of insulin detemir from 17.5 ± .22 U/kg at baseline to 27.7 ± .34 U/kg at the end of the study in the Lebanese population is in line with the 52-week follow-up results of PREDICTIVE TM study.…”
Section: Insulin Detemir In T2dm -Echtay Et Almentioning
confidence: 99%
“…Observational studies, including the A 1 chieve study, have provided support for this from routine clinical practice (9)(10)(11)(12).…”
mentioning
confidence: 97%
“…Accordingly, there is also a gain in life expectancy. Findings of improved metabolic outcomes in the short-term have been consistent with insulin detemir in T2D in both RCTs and observational studies, although the extent of the improvement is often not as large in the RCTs as in the studies done in routine clinical practice such as A 1 chieve 5,[13][14][15]17,19,21,23 . A 30-year time horizon was judged realistic, as most people in the modeled cohort would be expected to die within that time, and such a time horizon will allow the capturing of the relevant costs and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In randomized clinical trials (RCTs) in insulin-naïve people with T2D, basal insulin analogs have demonstrated better glycemic control with a lower risk of hypoglycemia compared with human neutral protamine Hagedorn (NPH) insulin [13][14][15][16][17][18] . Furthermore, the clinical effectiveness of basal insulin analogs in T2D has been demonstrated in real-life observational studies 5,[19][20][21][22][23] . Observational data are often collected from large heterogeneous populations that help enhance the generalizability of the clinical findings of RCTs.…”
Section: Introductionmentioning
confidence: 99%